2022
DOI: 10.1088/1748-9326/ac8be4
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hot and dry fuel conditions and vegetation dynamics in the 2017 fire season in Portugal

Abstract: Wildfires are a serious threat to ecosystems and human. In Portugal, during 2017, a catastrophic fire season burned more than 500 000 hectares and caused the death of more than 100 people. Previous studies have shown that hot and dry fuel conditions promoted widespread propagation of wildfires. However, burned area (BA) and mega-fires, such as the 2017 ones, depend not just on favourable meteorological conditions, but also on fuel accumulation and dryness. In this study, we will assess the influence of spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
2
4
0
Order By: Relevance
“…Moreover, the results also agree with Mateus and Fernandes' [63] observations, in the way that the extreme fire seasons in Portugal are strongly linked to the association of fuel accumulation availability with hot and dry conditions, which was also pinpointed by Gouveia et al [18] and Ermitão et al [19]. Some of the most susceptible areas to fire have burned in the last years, especially in 2017, when wildfires devastated the central part of the country [10,19,20]. Our analysis relied on a dataset of around 20 years (depending on the variable) and indicated that, despite the recent occurrence of fire events, those areas constitute a hotspot and have a great potential to burn in the near future.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, the results also agree with Mateus and Fernandes' [63] observations, in the way that the extreme fire seasons in Portugal are strongly linked to the association of fuel accumulation availability with hot and dry conditions, which was also pinpointed by Gouveia et al [18] and Ermitão et al [19]. Some of the most susceptible areas to fire have burned in the last years, especially in 2017, when wildfires devastated the central part of the country [10,19,20]. Our analysis relied on a dataset of around 20 years (depending on the variable) and indicated that, despite the recent occurrence of fire events, those areas constitute a hotspot and have a great potential to burn in the near future.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, although we do not directly address an analysis for hot and dry conditions in ecosystems, our results of fire weather conditions are in line with Pausas and Fernández-Muñoz's [62] insights. Moreover, the results also agree with Mateus and Fernandes' [63] observations, in the way that the extreme fire seasons in Portugal are strongly linked to the association of fuel accumulation availability with hot and dry conditions, which was also pinpointed by Gouveia et al [18] and Ermitão et al [19]. Some of the most susceptible areas to fire have burned in the last years, especially in 2017, when wildfires devastated the central part of the country [10,19,20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Apart from the documented association between droughts and heat extreme events in certain parts of the world, their influence on vegetation activity has been also analyzed during the last years. 5 , 24 , 25 , 26 , 27 , 28 Previous studies pointed out that the depletion of soil water content amplifies high temperatures due to the increase of sensible heat fluxes, 29 leading to a consequent reduction in the transpiration and photosynthetic activity of vegetation, 30 which on the other hand can lead to severe wildfires and consequently to considerable economic, social, and environmental damages. 31 Moreover, the land-atmosphere-vegetation interplay can occur with different levels of damage, even for low-intensity extremes, 32 and its highly dependent on the land cover.…”
Section: Introductionmentioning
confidence: 99%